Influence of Nutritional Support Methods on Postoperative Well-being in Pancreaticoduodenectomy Patients - Mozammel Haque, Md; Chandra Das, Bidhan; Masud Rana, Abunur Md; Ahmed, SM Ferdous; Quiyum, Md Abdul (Medicine Today, 2025)
Introduction: Early enteral feeding has gained attention as a potential method to enhance postoperative recovery in patients undergoing pancreaticoduodenectomy. Traditionally, postoperative feeding was delayed to stabilize intestinal anastomoses, but recent evidence suggests that early enteral feeding may offer significant advantages. By examining the effects of early versus delayed enteral feeding, we aim to understand its impact on postoperative outcomes and guide best practices in perioperative care. Materials and Methods: This prospective case-control study took place in the Department of Surgery of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. This study was conducted from 1st January to 31st December 2016. A total of 30 patients were selected as study subjects by purposive sampling technique. Patients were divided into two groups; case (Group I, n=15) and control (Group II, n=15). Statistical analysis of the results was obtained by using Statistical Packages for Social Sciences (SPSS-21.0). Statistical significance was set at p<0.05 and the confidence interval was set at 95% level. Result: The study compared early and delayed enteral feeding in pancreaticoduodenectomy patients. Demographic and preoperative nutritional statuses were similar between groups. Significant differences were observed in intraoperative metrics, with the case group showing less blood loss (540.00 ± 91.03 ml vs. 613.33 ± 83.38 ml, p=0.029) and shorter operation times (4.40 ± 1.12 hrs vs. 5.30 ± 0.65 hrs, p=0.012). Postoperatively, hemoglobin levels and lymphocyte counts increased more in the case group, indicating better recovery. Differences in surgical techniques also varied significantly between groups. Conclusion: This study evaluated the effects of early versus delayed enteral feeding on postoperative outcomes in pancreaticoduodenectomy patients. The results show that early enteral feeding enhanced lymphocyte counts, indicating better immune function. Medicine Today 2025, Vol.37 (1): 9-13